Prehospital Blood Transfusion During Aeromedical Evacuation of Trauma Patients in Israel: The IDF CSAR Experience. (1st March 2017) - Chen, Jacob; Benov, Avi; Nadler, Roy; Darlington, Daniel N.; Cap, Andrew P.; Lipsky, Ari M.; Glassberg, Elon
ABSTRACT: Background: Data regarding the effect of prehospital blood administration to trauma patients during short-to-moderate time evacuations is scarce. The Israel Air Force Airborne Combat Search and Rescue is the only organization that deals with aeromedical evacuation for both military and civilian casualties in Israel and the only one with the ability to give blood in the prehospital setting. Methods: Data on packed red blood cells (PRBCs) administration in the evacuation missions from January 2003 to June 2010 were analyzed and actual transfusion practice was compared to clinical practice guidelines (CPGs). Results: Over the studied 101 months, a total of 1, 721 patients were evacuated by Combat Search and Rescue. Of these, 87 (5.1%) trauma patients were transfused with PRBC. Demographics included 83% male and 17% female with a median age of 23 years. Main mechanisms of injury included gunshot wounds (36%), motor vehicle accidents (28%), and blast injuries (24%) with an average of 2.6 injured regions per casualty. The most commonly injured body regions included lower extremities (52%), chest (45%), and abdomen (38%). Overall, 10 (11%) casualties died. Lifesaving intervention included tourniquets (27%), endotracheal intubation (24%), tube thoracostomy (24%), and needle thoracostomy (21%) times. For 98% of the patients, clinical judgment led to administration of red blood cells before indicated by the CPG. The heart rate tended to decrease during the evacuation, whereas there was no clear trend in systolic or diastolic blood pressure or shock index. Conclusions: In our aeromedical experience, transfusion of PRBCs for trauma patients was safe, feasible, and most likely beneficial. PRBCs were administered according to the flight surgeons' clinical judgment and not in complete adherence to CPGs in most cases. Data collected from this and similar studies worldwide have led to change in CPGs with the shift from hypertensive resuscitation to hypotensive-hemostatic Remote Damage Control Resuscitation.